Primary Care Careers Among Recent Graduates of Research-Intensive Private and Public Medical Schools - Choi, Phillip A. (Springer-Verlag, 2012)
BACKGROUND: Despite a growing need for primary care physicians in the United States, the proportion of medical school graduates pursuing primary care careers has declined over the past decade. OBJECTIVE: To assess the association of medical school research funding with graduates matching in family medicine residencies and practicing primary care. DESIGN: Observational study of United States medical schools. PARTICIPANTS: One hundred twenty-one allopathic medical schools. MAIN MEASURES: The primary outcomes included the proportion of each school’s graduates from 1999 to 2001 who were primary care physicians in 2008, and the proportion of each school’s graduates who entered family medicine residencies during 2007 through 2009. The 25 medical schools with the highest levels of research funding from the National Institutes of Health in 2010 were designated as “research-intensive.” KEY RESULTS: Among research-intensive medical schools, the 16 private medical schools produced significantly fewer practicing primary care physicians (median 24.1 % vs. 33.4 %, p < 0.001) and fewer recent graduates matching in family medicine residencies (median 2.4 % vs. 6.2 %, p < 0.001) than the other 30 private schools. In contrast, the nine research-intensive public medical schools produced comparable proportions of graduates pursuing primary care careers (median 36.1 % vs. 36.3 %, p = 0.87) and matching in family medicine residencies (median 7.4 % vs. 10.0 %, p = 0.37) relative to the other 66 public medical schools. CONCLUSIONS: To meet the health care needs of the US population, research-intensive private medical schools should play a more active role in promoting primary care careers for their students and graduates. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11606-012-2286-z) contains supplementary material, which is available to authorized users.